ChemInform Abstract: Two Dihydroxo‐Bridged Plutonium(IV) Nitrate Dimers and Their Relevance to Trends in Tetravalent Ion Hydrolysis and Condensation. Issue 2 (23rd December 2015) - Knope, Karah E.; Skanthakumar, S.; Soderholm, L.
Abstract: Single crystals of [Pu2 (OH)2 (NO3 )6 (H2 O)4 ]2 ·11H2 O (I) and Pu2 (OH)2 (NO3 )6 (H2 O)4 ·2H2 O (II) are obtained by evaporation of aqueous stock solutions of 25 mM 242 Pu in 4 M HNO3 .